PULMONARY FUNCTION TEST IN A COHORT OF OLDER PAKISTANI POPULATION - Memon, Muhammad Asif; Sandila, Muhammad Perwaiz (Pakistan Journal of Physiology, 2006)
Background: Pulmonary function test (PFT) depends on a number of factors as height, age, gender and race. Reference equations are used to determine a normal range of spirometry results which in turn are used clinically to determine whether the volumes measured in any individual fall within a range to be expected in a healthy person of the same gender, height and age. Methods: The study was conducted in Karachi on 249 healthy, nonsmoking subjects between 35 to 65 years of age were included in the study. The subjects included 149 ma les and 100 females whose pulmonary volumes and capacities were measured by spirometry. Results: Prediction equation was first derived and the reference values were then calculated for FEV1 and FVC. The values for both these parameters were found to be lower by about 13% and 18% in females and 10% and 12% in males respectively when compared with those given by researchers for Caucasians. Conclusion: Pulmonary function test reference values and prediction equations for both sexes between the ages of 35-65 years were derived for healthy, nonsmoking, urban Pakistani population. A considerable difference was found between prediction equations and reference values obtained in present study compared with other studies conducted in western countries.